PENINGKATAN HASIL BELAJAR IPS MELALUI MODEL PROJECT BASED LEARNING KELAS IV SDIT AL KAWAAKIB JAKARTA BARAT - Ajat Sudrajat; Ika Budiarti (WASIS : Jurnal Ilmiah Pendidikan, 2020)
The pupose of this study was to increase students attention and learning outcomes on social studies learning content through the project based learning approach in class IV at SDIT Al Kawaakib. The research subjects were student of class IV with 11 students consist of male 7 students, female 4 students. This research was conducted on february 1 s.d February 29, 2020. Even semester of the 2019/2020 school year. Based on the results of the study, it shows that student learning outcomes increase with increasing student attention and interes in social studies learning materials through a project-based learning approach. This can be sen from the student learning outcomes in the form of learning completeness which increased up to 73% at the end of cycle 2. The conclusion of this study shows that the Project Based Learning model can increase interest and learning outcomes of fourth grade students of SDIT Al Kawaakib